Development and validation of a PCR-based assay for the selection of patients more likely to benefit from therapeutic treatment with alkylating drugs - Stefanou, D.T.; Episkopou, H.; Kyrtopoulos, S.A.; Bamias, A.; Gkotzamanidou, M.; Bamia, C.; Liakou, C.; Bekyrou, M.; Sfikakis, P.P.; Dimopoulos, M.-A.; Souliotis, V.L. (British Journal of Clinical Pharmacology, 2012)
AIM In order to develop and validate a simple, sensitive and rapid method for the quantitation of alkylating drug-induced DNA damage. METHODS HepG2 cells and blood samples were treated with alkylating drugs (melphalan, cisplatin, carboplatin). Gene-specific damage was examined using Southern blot and a multiplex long quantitative PCR (QPCR) carried out in a 7kb fragment (part of the p53 gene) and a 0.5kb fragment (part of the IFN-β1 sequence; internal standard). RESULTS The extent of PCR amplification of a p53 fragment was inversely proportional to the treatment concentrations of all anticancer drugs examined, indicating a dose-related inhibition by the DNA adducts formed. Parallel analysis of the same samples using both Southern blot and QPCR showed that the DNA adducts measured by QPCR corresponded to the interstrand cross-links in the case of melphalan, and to total drug-induced lesions in the case of the platinum drugs. The detection limit was ∼10-20 lesions/106 nucleotides using DNA from ∼8000 cells. The method is about 250 times more sensitive than the Southern blot-based method and the reproducibility is excellent, with an intraday coefficient of variance (CV) of 5-9% and an interday CV of 4-12%. Application of the QPCR assay to ex vivo melphalan-treated peripheral blood mononuclear cells from multiple myeloma patients, showed that the positive predictive value of this assay for clinical response to melphalan therapy was 92.9%. CONCLUSION The PCR-based assay developed in this study can be used for the selection of cancer patients more likely to benefit from therapeutic treatment with alkylating drugs. © 2012 The Authors. British Journal of Clinical Pharmacology © 2012 The British Pharmacological Society.
Keywords: Alkylating drugs; Clinical outcome; DNA adducts; DNA repair; Multiplex quantitative PCR